Obsessive-compulsive disorder : serotonergic and dopaminergic system involvement in symptom generation and treatment response - Carey, Paul D. (Paul Dermot) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2008.